Impact of rich cultural tourism experience on tourist satisfactions and behavioral intentions toward Ningxia’s cultural heritage: Moderation role of perceived cultural distance - Lei Qin; Hongmei Zhang (PLoS ONE, 2025)
Ningxia is a renowned cultural tourism destination with rich heritage and natural landscapes. Current research, however, remains unclear on how multi-dimensional cultural experiences influence tourist behavior-particularly the mediating role of cultural identity (CI) and the moderating effect of perceived cultural distance (PCD). To address this gap, this study expands the Cognitive-Affective-Behavioral model and examines how Rich Cultural Tourism Experiences (RCTE) affect satisfaction and behavioral intentions, using network semantic analysis (14,163 texts) and PLS-SEM (547 questionnaires). Five RCTE dimensions are identified: historical, modern, folk, spiritual, and ecological. Results show that RCTE boosts satisfaction, which in turn enhances behavioral intentions. Among the dimensions, spiritual, historical, and ecological experiences exert the strongest effects on CI, with path coefficients of 0.247, 0.244, and 0.200 respectively. CI serves as a key mediator, while PCD weakens RCTE’s impact on CI-but not on satisfaction.